My first ABC board book - Wardley, Rachel (Dorling Kindersley London, 2010)
The best-selling My First series - now brighter, bolder and better! Make A, B, C as easy as can be with My First ABC Board Book. Packed with bright, lively pictures and large, simple text, this is an ideal book to stimulate recognition and encourage talking and naming. Chunky format and hardwearing pages are great for little hands